Bile Duct Varices ''Pseudo-Cholangiocarcinoma Sign" in Portal Hypertention Due to Cavernous Transformation of The Portal Vein - Yusuf BAYRAKTAR; Ferhun BALKANCI; Serap ARSLAN; Burhan KAYHAN; Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-